Blockchain Readiness Assessment For Malaysian Organizations And Challenges To Adopt Blockchain Technology - Teoh, Chin Xuan (Universiti Sains Malaysia, 2021)
Blockchain as an inspiring emerging kind of technology, is capable to create disruptive effects to many industries and organizations as well as the existing way of human life now. Blockchain technology comes with many benefits in the form of providing transparency, reducing costs, immutability and security. However, an in deep investigation and analysis about readiness level have to be conducted before blockchain can be widely implemented in Malaysia as pre-determining readiness level and challenges will help to adopt the technology smoothly. This study aims to calculate and compare the readiness score among Malaysian organizations on the acceptance and adoption of blockchain technology into their businesses, identify and analyse challenges faced by them, as well as to suggest some practical advices to achieve optimization of blockchain technology based the readiness level and difficulties they had. The research methodology starts with a systematic review of the blockchain related literature through online searching for the journal articles. After project planning was done, a questionnaire was constructed for collecting both quantitative and qualitative data from the respective Malaysian organizations’ respondents. Subsequently, the final readiness scores were calculated using weighted mean and linear mapping equations. The results indicate that the overall blockchain readiness score among Malaysian organizations is at slightly below average level (46.3%). Organization C ranked number one with highest readiness score while organization D has lowest readiness score. The major challenges are possible security threat and lack of blockchain talent. Key motivations are transparency and efficiency improvement with creation of competitive advantages. IT computing skill, programming knowledge, innovation, strong analytic skill, standardize regulation, data management quality, training provided are among the essential skills and strategies for keeping up the future success of blockchain technology. The limitation of this study is the reducing of range and quantity of responses that had been successfully collected from respondents due to restricted movement during this Covid-19 pandemic. Generally, the objectives were achieved throughout the end of this project. This study provide insight to readers about the current degree of preparedness and point of views among Malaysian organizations towards the blockchain technology as well as provide a useful quality reference source for practitioners who are interested in blockchain technology.